Development of e-Module Based on a Scientific Approach By Teachers of SMAN 3 Padang Panjang - Budhi Oktavia; Guspatni Guspatni; Miftahul Khair; Fajriah Azra (Fakultas MIPA Universitas Negeri Padang, 2020)
This society service was done at the request from teachers of SMAN 3 Padang Panjang in 2019. In this activity, teachers were given materials on technology based media and techniques to develop it accordingly to the demand of national curriculum. 20 teachers followed the activity that began with the installation of ebook maker program, tutorial on getting and editing media from online resources, introduction to appropriate learning media, development of e-module integrating video, audio, animation, hyperlink and other interactive features, and distribution of Likert scale questionnaire on the last day of the activity. Data showed that terachers had facilities, access and support to implement technology based learning. E-module got positive response from teachers of SMAN 3 Padang Panjang, for it is perceived to be capable of delivering learning material and evaluation effectively.